2009
DOI: 10.1007/s00421-009-1320-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of training status and exercise modality on pulmonary O2 uptake kinetics in pre-pubertal girls

Abstract: The limited available evidence suggests that endurance training does not influence the pulmonary oxygen uptake (V(O)(2)) kinetics of pre-pubertal children. We hypothesised that, in young trained swimmers, training status-related adaptations in the V(O)(2) and heart rate (HR) kinetics would be more evident during upper body (arm cranking) than during leg cycling exercise. Eight swim-trained (T; 11.4 +/- 0.7 years) and eight untrained (UT; 11.5 +/- 0.6 years) girls completed repeated bouts of constant work rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
31
4

Year Published

2010
2010
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 67 publications
8
31
4
Order By: Relevance
“…It has, however, previously been demonstrated that the menstrual phase has no effect on the p 2 o V  or HHb kinetics (Gurd et al 2007). The sample sizes were small, but were in accord with previous work published in this area (McNarry et al 2011;Winlove et al 2010). Furthermore, the lack of significant differences in HHb kinetics was offset by the large effect sizes.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…It has, however, previously been demonstrated that the menstrual phase has no effect on the p 2 o V  or HHb kinetics (Gurd et al 2007). The sample sizes were small, but were in accord with previous work published in this area (McNarry et al 2011;Winlove et al 2010). Furthermore, the lack of significant differences in HHb kinetics was offset by the large effect sizes.…”
Section: Discussionsupporting
confidence: 74%
“…Earlier evidence from cross-sectional studies seemed to indicate that exercise training had no effect in reducing the time constant of the fundamental phase of p 2 o V  kinetics in pre-pubertal children (Cleuziou et al 2002;Obert et al 2000). More recent cross-sectional studies, however, have demonstrated that systematic exercise training may result in a speeding of the fundamental phase of p 2 o V  kinetics in both children (Winlove et al 2010) and adolescents (Marwood et al 2010, McNarry et al 2011. Such discrepancies may be explained by the lack of congruence between the training and experimental exercise modality in the earlier studies (Cleuziou et al 2002;Obert et al 2000).…”
mentioning
confidence: 98%
“…Indeed, the importance of exercise modality to the investigation of training status influences on _ VO 2 kinetics has previously been reported in pre-pubertal girls where effects were evident in upper body but not lower body exercise (Winlove et al 2010). …”
Section: Introductionmentioning
confidence: 95%
“…Bailey et al 2009;Koppo et al 2004;Powers et al 1985). The temporal features of the _ VO 2 response have similarly been shown to be influenced by training status in pre-pubertal children, provided that an appropriate test modality is used (Winlove et al 2010), although this remains controversial (Cleuziou et al 2002;Obert et al 2000).…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, it has recently been shown that during the 2-year period between the ages of 14 and 16 years old the fundamental phase of pulmonary oxygen uptake kinetics slows and the contribution of the slow component increases during heavy intensity exercise (Breese et al 2010), therefore becoming characteristic of the adult response to exercise. We have recently demonstrated faster pulmonary oxygen uptake kinetics during the transition to moderate-intensity exercise in a group of trained male adolescents as compared to an untrained control group (Marwood et al 2010) which is a feature of the trained state both in adults and children (Jones and Koppo 2005;Winlove et al 2010). …”
Section: Introductionmentioning
confidence: 99%